Additive Manufacturing of Multi-material Polymer Parts Within the Collaborative Research Center 814 - Setter, Robert; Stichel, Thomas; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Roth, Stephan; Wudy, Katrin (Lecture Notes in Mechanical Engineering, 2021)
During the past years additive manufacturing (AM) has revolutionized the manufacturing world by enabling rapid generation of geometrically-intricate designs. However, up to now in laser and beam-based AM of polymers only single powder materials whether filled or pure plastics can be processed. One aim of the Collaborative Research Center 814 (CRC 814) – Additive Manufacturing is to establish new process technologies to produce multi-material polymer parts in AM. Therefore, two different strategies basing on Laser Sintering (LS) will be explored: On the one side, selective powder deposition technologies like vibrating nozzles or electrophotography are investigated, which enable to lay down different powders beside each other in one process. On the other side, a liquid reactive UV-curing thermoset is implemented into the LS process chamber. After curing of the UV-curing thermoset the powder beside the cured thermoset is molten by the use of the CO2 laser. Both strategies allow the generation of multi-material parts consisting of material regions with different functional properties.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Additive Manufacturing; Binder Jetting; Laser Sintering; Multi-material parts

Additive manufacturing of polyamide 12 bulk structures using directed energy deposition with a thulium laser: Effect of process conditions on morphology and mechanical performance - Wittmann, Alexander; Meth, Claudia; Alidoust Chamandani, Saeed; Vetter, Johannes; Kopp, Sebastian-Paul; Schmidt, Michael (Journal of Laser Applications, 2024)
Laser-based directed energy deposition of polymers (DED-LB/P) is a highly flexible additive manufacturing process capable of fabricating three-dimensional structures with a high degree of customization on free-form surfaces. In this article, the manufacturability of polyamide 12 bulk structures using DED-LB/P in combination with a thulium laser operating at a wavelength of 1.94 μm is investigated for the first time. The typical absorption bands at this wavelength eliminate the need for additives such as carbon-based nanoparticles, which would limit the range of applications. The generated structures were analyzed regarding porosity, thermal behavior, and mechanical properties to evaluate the potential of DED-LB/P with a thulium laser. As a consequence of the evaporation of absorbed moisture or ethanol residues resulting from powder preparation, a thermal pretreatment of the polymer powder reduced the porosity of the DED-LB/P structures to 0.9%. Depending on the processing parameters, the crystallinity of the produced structures ranged from 25.6% to 29.9%. For the tensile tests, the required geometries were milled from the DED-LB/P bulk structures. The results show that an ultimate tensile strength of up to 52 MPa, an elongation at break of up to 58%, and Young's modulus of up to 1590 MPa can be achieved. These remarkable mechanical properties are primarily attributed to the complete melting of the powder particles in DED-LB/P and the improved surface quality resulting from the milling proces
Keywords: Materials properties; Polymers; Laser materials processing; Lasers

Advanced laser irradiation strategies for tailoring temperature profiles for laser-based powder bed fusion (PBF-LB/P) of highly absorbing polymers - Medvedev, Vadim; Kopp, Sebastian-Paul; Roth, Stephan (Lasers in Manufacturing Conference 2023, 2023)
Additively manufactured parts consisting of polymer powders blended with carbon black have increased protection against ultraviolet radiation and thus are beneficial for applications involving intensive exposure to sunlight. However, this powder blends are challenging to be processed in laser-based powder bed fusion of polymers (PBF-LB/P) due to their high absorptivity of infrared radiation. Thus, precisely tailoring the energy input provided by a CO2-laser is crucial for enhancing process stability for processing highly absorptive polymers. Adapting the laser energy input by applying advanced irradiation strategies offers the possibility to tailor the temperature profiles during PBF-LB/P process. In this study, the effect of advanced laser irradiation strategies with pixel-encoded energy densities on the adaption of the temperature profile of polymer powders blended with carbon black is investigated. Finally, irradiation patterns are defined to achieve spatially tailored temperature profiles across the powder layer for demonstration the capabilities of the developed scanning strategy.<br
Keywords: Laser powder bed fusion; laser illumination strategy; carbon black; temperature profile; selective laser sintering

Bottom-Up Design of Composite Supraparticles for Powder-Based Additive Manufacturing - Canziani, Herbert; Chiera, Salvatore; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Metzger, Florian; Bück, Andreas; Schmidt, Michael; Vogel, Nicolas (Small, 2020)
Additive manufacturing promises high flexibility and customized product design. Powder bed fusion processes use a laser to melt a polymer powder at predefined locations and iterate the scheme to build 3D objects. The design of flowable powders is a critical parameter for a successful fabrication process that currently limits the choice of available materials. Here, a bottom-up process is introduced to fabricate tailored polymer- and composite supraparticles for powder-based additive manufacturing processes by controlled aggregation of colloidal primary particles. These supraparticles exhibit a near-spherical shape and tailored composition, morphology, and surface roughness. These parameters can be precisely controlled by the mixing and size ratio of the primary particles. Polystyrene/silica composite particles are chosen as a model system to establish structure–property relations connecting shape, morphology, and surface roughness to the adhesion within the powder, which is accessed by tensile strength measurements. The adhesive properties are then connected to powder flowability and it is shown that the resulting powders allow the formation of dense powder films with uniform coverage. Finally, successful powder bed fusion is demonstrated by producing macroscopic single layer specimens with uniform distribution of nanoscale silica additives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: additive manufacturing; composite powders; nanoscale; spray drying; supraparticles

Correlation of optical energy onto nano-Additivated CuS/PA12 and LaB6/PA12 powder with depth of fusion in PBF-LB/P - Leupold, Simon; Willeke, Michael; Leong, Cheechau; Stratmann, Nadine; Sommereyns, Alexander; Ziefub, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Procedia CIRP, 2024)
The printability in laser powder bed fusion of polymers is significantly depended on the absorption of the laser light and the energy density provided by the laser. Most commonly, a CO2 laser is used for PBF-LB/P requiring no additional absorbers. However, when utilizing near-infrared diode lasers, additional absorbers are needed as the polymers themselves do not absorb enough energy at this wavelength. The interactions of light, polymer and absorbers have yet to be fully understood. In this study, the absorptance and resulting geometry of polyamide 12 coated with CuS and LaB6 nanoparticles, made by high-power laser-fragmentation, were analyzed. Multilayer samples consisting of five layers were manufactured at specific energy densities, using a 808 nm PBF-LB/P diode laser setup, and the resulting dimensions were measured. The results suggest that the nanoparticle intrinsic properties can significantly affect resulting geometrical accuracy, even for small quantities of nanoparticles.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Copper monosulfide nanoparticles; Lanthanum hexaboride nanoparticles; NIR Laser; PA12; PBF-LB/P

Efficient shielding gas supply for laser-based Powder Bed Fusion of metals (PBF-LB/M) - Medvedev, Vadim; Kopp, Sebastian-Paul; Nahr, Florian; Roth, Stephan (Procedia CIRP, 2024)
The inert gas supply during laser-based powder bed fusion of metals (PBF-LB/M) is one of the most important sub-processes influencing the quality of the end products and the efficiency of the printing process. However, improper distribution of the shielding gas flow can result in poor part quality and excessive energy and gas consumption. Thus, the formation of a homogeneous protective gas flow over the powder melting region is crucial to minimize the negative effects mentioned above. In this investigation, a modified system for supplying shielding gas to the building chamber of PBF-LB/M machine is developed with the possibility of creating localized and uniform gas flows over the area where the melting process takes place. The aim of the selectively localizable shielding gas supply is to improve process efficiency of PBF-LB/M while giving the opportunity to enhance part properties such as surface roughness.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Additive Manufacturing; AlSi10Mg; process efficiency; Selective laser melting; shielding gas flow

Electrophotographic 3D printing of pharmaceutical films - Kopp, Sebastian-Paul; Medvedev, Vadim; Tangermann-Gerk, Katja; Wöltinger, Natalie; Rothfelder, Richard; Graßl, Fabian; Heinrich, Markus; Januskaite, Patricija; Goyanes, Alvaro; Basit, Abdul W.; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
The usage of three-dimensional (3D) printing in pharmaceutical applications offers significant advantages compared to conventional manufacturing approaches such as tableting or encapsulation. Laser sintering (LS), also referred to as powder bed fusion – laser beam (PBF-LB), formerly also known as selective laser sintering (SLS), offers the production of pharmaceuticals directly from a powder mixture with high geometrical flexibility and adjustable release profiles. However, due to limitations of conventional powder application methods for PBF-LB, neither the material composition nor the material distribution can be tailored within a printed layer. To overcome these restrictions, electrophotographic powder application (EPA), a novel method for selective powder application, was utilized in this study. EPA allows the deposited layer thickness to be reduced to values between 12 and 76 µm, depending on the used pharmaceutical powder blend. Thus, the laser energy input required for interlayer connection can be reduced, enabling the use of a CO2 laser. In this study, for the first time, EPA in combination with powder bed fusion – laser beam of polymers (EPA-PBF-LB/P) was utilized to successfully deposit and print three different model drugs: paracetamol, nicotinamide, and caffeine, mixed with Eudragit L 100–55, a pharmaceutical grade polymer. Through the use of EPA, thin layers of powder blends were successfully deposited in the build chamber, leading to no thermal degradation of the polymer or drugs from the use of a CO2 laser. Single- and multi-material pharmaceutical films were successfully printed via EPA-PBF-LB, utilizing EPA to selectively as well as precisely apply different powders within a single layer into the build chamber. This introduces a novel method of printing pharmaceuticals using SLS with a CO2 laser and without the use of additional colorants.<br
Keywords: Additive manufacturing; Electrophotography; Printed pharmaceuticals; Laser powder bed fusion; Laser sintering; Multi-material printing

Electrophotographic Powder Application for Surface Functionalization of Polymer Parts with Thin Silver‐Nanoadditivated Bactericidal Layers - Kricke, Jan Lino; Ebert, Niklas; Sorarrain, Ane; Roth, Stephan; Fischer, Dagmar; Schmidt, Michael; Gökce, Bilal; Marimón, José María; Kopp, Sebastian-Paul; Doñate‐Buendía, Carlos (Advanced Materials Technologies, 2025)
The feedstock in laser beam powder bed fusion of plastics (PBF-LB/P) is typically limited to a few materials with strict flowability requirements and low recycling rates, compromising its economic efficiency and sustainability. Polymer nanoadditivation gains attraction to tailor their physiochemical properties by incorporating nanoadditives. Herein, a new approach is introduced to functionalize polymer part surfaces via electrophotographic powder application (EPA). Polyamide 12 (PA 12) microparticles decorated with laser-synthesized silver nanoparticles (Ag NPs) are printed as thin layers on bulk PA 12 parts. The coating provides bactericidal functionality to the printed part with reduced nanoadditive employment. Indeed, only two Ag-PA 12 layers accounting for a 140 µm thick coating inhibit S. aureus and E. coli bacteria growth. As a result of the low coating thickness and Ag NP loading of only 0.1 wt.%, the mechanical and calorimetric properties remain unaffected. Owing to its versatility, the proposed approach is envisioned to facilitate selective surface functionalization toward graded materials printing at reduced costs and waste generatio

Enabling triboelectric charging as a powder charging method for electrophotographic powder application in laser-based powder bed fusion of polymers by triboelectric charge control - Kopp, Sebastian-Paul; Düsenberg, Björn; Eshun, Pius Marcellinus; Schmidt, Jochen; Bück, Andreas; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
Substituting conventional doctor blade- or roller-based powder application methods for laser-based powder bed fusion of polymers (PBF-LB/P) by electrophotographic powder application (EPA) offers significant advantages. In particular, the selective powder deposition enabled by EPA allows high powder efficiency and the possibility to locally adjust part properties during their fabrication. However, defined charging of powder particles is crucial for achieving an accurate selective deposition of powder layers by means of electrophotography. This is the first comprehensive study on the specific triboelectric charge control of polymer particles for their subsequent use in electrophotographic powder application for PBF-LB/P. For this purpose, approaches for charge control of toner particles in the context of digital (2D) printing technologies are adapted and applied to polypropylene (PP) feedstocks for PBF-LB/P. In order to show transferability to other polymers, the charge control method developed in this paper is also applied to polyamide 12 (PA12) high density polyethylene (HDPE) and polystyrene (PS). For successful EPA, unipolar charging of polymer particles is crucial. However, non-functionalized PP shows a strongly bipolar triboelectric charging, which is unsuitable for EPA. The charge control method developed in this work shifts this strongly bipolar triboelectric charging to a unipolar charging. This is achieved by the synergy of both functionalizing the particle surface with charge control agents (CCAs) and choosing suitable carrier particles known from two-component toners. The developed method allows to control crucial parameters of triboelectric charging, namely polarity, amount of charge and resulting surface potential. Furthermore, the presented results provide new insights into the transfer behavior of charged PP particles in an external electric field. Finally, this enables the triboelectric charging mechanism to be used for electrophotographic powder application in PBF-LB/P.<br
Keywords: Charge control Electrophotography Triboelectric charging Laser powder bed fusion Polymer particles Powder application

Enhancing Photoelectric Powder Deposition of Polymers by Charge Control Substances - Düsenberg, Björn; Kopp, Sebastian-Paul; Tischer, Florentin; Schrüfer, Stefan; Roth, Stephan; Schmidt, Jochen; Schmidt, Michael; Schubert, Dirk W.; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Charge control substances (CCS) as additives for polymer powders are investigated to make polymer powders suitable for the electrophotographic powder deposition in powder-based additive manufacturing. The use of CCS unifies the occurring charge of a powder, which is crucial for this novel deposition method. Therefore, commercially available polymer powder is functionalized via dry coating in a shaker mixer with two different CCS and analyzed afterwards. The flowability and the degree of coverage of additives on the surface are used to evaluate the coating process. The thermal properties are analyzed by use of differential scanning calorimetry. Most important, the influence of the CCS on the powder charge is shown by measurements of the electrostatic surface potential at first and the powder deposition itself is performed and analyzed with selected formulations afterwards to show the potential of this method. Finally, tensile strength specimens are produced with the conventional deposition method in order to show the usability of the CCS for current machines.<br
Keywords: additive manufacturing; charge control substances; photoelectric powder deposition; polypropylene; dry coating

Expanding the capabilities of laser-based powder bed fusion of polymers through the use of electrophotographic powder application - Kopp, Sebastian-Paul; Medvedev, Vadim; Frick, Thomas; Roth, Stephan (Journal of Laser Applications, 2022)
Generating multimaterial parts, reaching higher efficiency in powder consumption, and decoupling of powder application behavior from powder properties such as powder flowability are key aspects for using electrophotographic powder application (EPA) in laser-based powder bed fusion of polymers (PBF-LB/P). Moreover, EPA allows the layer thickness to be reduced from around 100–150 μm, depending on respective particle size distribution, in the case of conventional doctor blade or roller-based powder application methods to the diameter of the applied polymer particles (typically between 50 and 130 μm). This can have positive effects on the interlayer connection and, therefore, the mechanical properties of the additively manufactured part because less powder volume has to be fused with the already generated underlying part. Moreover, due to the above-mentioned independence of EPA from powder flowability, the addition of flow aids, such as nano silica, can be reduced to a minimum or even avoided completely. This is the first comprehensive study on resulting properties of parts generated by PBF-LB/P using EPA taking into account both the reduction in layer thickness and reduced addition of flow aids. In addition to improving mechanical properties of generated parts, the independence of powder flowability, in particular, offers the possibility of qualifying currently unsuitable materials for PBF-LB/P. For this purpose, besides widely employed polyamide 12 (PA12), a polypropylene (PP) powder is used that is very difficult to process in conventional PBF-LB/P and can only be applied there with the help of flow aid

Functional polyetheretherketone coatings fabricated by laser-based directed energy deposition - Wittmann, Alexander; Alidoust Chamandani, Saeed; Hentschel, Oliver; Sommereyns, Alexander; Kopp, Sebastian-Paul; Schmidt, Michael (Surface & Coatings Technology, 2025)
In this paper, directed energy deposition of polymers (DED-LB/P) with a thulium laser is investigated for the first time to apply functional polyetheretherketone coatings on stainless steel 316L sheets. Powder feeding experiments in this study show that the irregular particle shape and fine particles of the raw polyetheretherketone powder lead to low powder mass flows and a high tendency to agglomeration during DED-LB/P processing. Due to the altered surface topography, heat-treating the polymer powder results in stable powder feeding conditions with a reproducibly adjustable powder mass flow. A multi-pass deposition strategy with a gentle energy input maintains process stability and prevents thermal decomposition of the polyetheretherketone powder in DED-LB/P. The absence of pores in the cross-sectional examination indicates that coatings with a high density can be deposited. Furthermore, the fabricated coatings exhibit a semi-crystalline structure and an excellent bond strength to the metallic substrate. In order to reduce the roughness of the coatings, an additional laser remelting step represents an appropriate process strategy. The characterization of the coated stainless steel 316L substrates shows that the DED-LB/P process has no decisive effect on the hardness, while the dimensional accuracy is slightly affected. Based on the polyetheretherketone coatings produced in this study, DED-LB/P with a thulium laser may have great potential for future medical applications because there is no need to add flow and absorbing additives to the polymer powde
Keywords: PEEK; Polyetheretherketone; Coating; Laser material processing; Directed energy deposition; Additive manufacturing

Geometry‐Based Scan Curve Analysis: Rapid Method for the Evaluation of Scan Strategies in Powder Bed Fusion - Leupold, Simon; Willeke, Michael; Sommereyns, Alexander; Gehring, Matthias; Dineshbhai, Parmar Yankit; Stratmann, Nadine; Ziefuss, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Advanced Engineering Materials, 2025)
It is well known that scan strategies have an essential role in powder bed fusion (PBF). For the comparison of different scan strategies, however, it is usually necessary to evaluate manufactured samples or run simulations. Given the typically lengthy nature of these processes, this study focuses on finding a rapid preprocess evaluation method for scan strategies using geometrical approaches: line buffer-based calculations and a point density field. Both approaches only depend on the geometry of the scan strategy. While these calculations should apply to most PBF processes, this study uses the evaluation methods to predict the differences that four unique scanning strategies have in PBF of polymers using an near-infrared laser source. Polyamid 12 powder with Lanthanum hexaboride nanoparticles and a commercial black-dyed Polyamid 12 powder are used for processing. The calculation of the line buffer-based surface energies of these scanning strategies correctly predicted the sequence in which the scanning curve appeared to have received the laser energy. Moreover, the defects observed in the manufactured samples appear to be related to the variation in point density of the scanning strategies. These promising results are the first step towards new preprocess evaluation methods, leading to improved predictability of different scan strategie
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; numerical simulations; process characterizations; rapid evaluation methods; toolpath generation

Herausforderungen der additiven Fertigung von Multi-Material-Bauteilen - Kopp, Sebastian-Paul; Stichel, Thomas; Schuffenhauer, Thomas; Roth, Stephan; Schmidt, Michael (Additive Fertigung: Vom Pulver zum multifunktionalen Bauteil, 2019)
Additive Fertigungstechnologien ermöglichen die schichtweise Generierung von Bauteilen mit komplexen Geometrien. Hierbei können schnell und individuell notwendige Formanpassungen im Produktentstehungszyklus durchgeführt werden, was einen entscheidenden Vorteil gegenüber herkömmlichen spanenden und nicht-spanenden Fertigungsverfahren bringt [1]. Bisher sind additive Technologien jedoch auf die Verwendung eines einzelnen Werkstoffes beschränkt. Die Herstellung von Multi-Material-Bauteilen, bestehend aus verschiedenen Kunststoffpulvern ähnlicher oder stark unterschiedlicher thermischer Verarbeitungseigenschaften, ist Gegenstand aktueller Forschung [2-4]. Basierend auf dem bereits etablierten Verfahren des Laserstrahlschmelzens von Kunststoffen (LSS-K) wird hierfür die Prozessroute so angepasst und erweitert, dass komplexe Werkstoffverbunde aus unterschiedlichen thermoplastischen Kunststoffen erzeugt werden können. Dies erfordert die Realisierung von definierten, heterogenen Pulververteilungen sowie deren Verarbeitung durch eine geeignete Bestrahlungsstrategie. Im vorliegenden Beitrag wird zunächst die entwickelte Bestrahlungsstrategie, welche die Herstellung von Bauteilen aus polymeren Werkstoffen mit unterschiedlichen thermischen Eigenschaften ermöglicht, thematisiert. Ferner werden der Multi-Material-Auftrag mittels Vibrationsdüsen sowie die hierfür speziell angepasste Bestrahlungsstrategie erläutert. Ausgehend von den Limitationen des vibrationsinduzierten Pulverauftrags wird schließlich das elektrophotographische Auftragsverfahren näher betra
Keywords: Additive Fertigung; Selektives Lasersintern; Multi-Material

Holistic Characterization of PBF-LB/P Powder Regarding Isothermal Crystallization, Rheology and Optical Properties Under Process Conditions - Marschall, Maximilian; Cholewa, Simon; Kopp, Sebastian-Paul; Drummer, Dietmar; Schmidt, Michael (Additive Manufacturing in Multidisciplinary Cooperation and Production, 2023)
Laser based powder bed fusion of Polymers is an additive manufacturing technology that meets requirements of established manufacturing processes; thus, it is essential to expand the original range of applications from prototype generation to functional components. Semi-crystalline materials, mainly polyamide 12 (PA 12), dominate the market. Prior to solidification, material crystallization takes place during the building phase, yielding changes in material properties including rheology and optical properties. To gain a deep process understanding for reliable part production, a process-adapted evaluation is required to ascertain how long the molten polymer remains amorphous with reduced absorption and viscous dominant behavior, to the point when crystallites are forming. In this contribution, the effect of solidification on optical characteristics during an isothermal process is discussed. The goal of this process adapted characterization method is to reduce feedback circles for powder development, discretize process parameter settings, and obtain a wide range of process relevant material characteristics for PBF-LB/P for the first time in such an integrated manner. This contribution compares temperature-dependent optical properties of a polymer powder layer and melt to rheological behavior of the isothermally solidifying melt pool. To ensure this comparability, both measurement setups are equipped with IR spectroscopy, which allows to analyze the isothermal crystallization progress. A modified double integrating sphere setup with FTIR (Fourier-transform infrared spectroscopy) and a rheometer with ATR (attenuated total reflection) were used. It was found out, that the isothermal crystallization already occurs faster than thought, even within preheating temperatures significantly above crystallization temperature in the upper layers. Thus, curling and thickness variation can appear due to change in absorptance and rheology, and impact the manufacturing quality. This can be a failure criterium for development stage of tailored polymer powders for PBF-LB/P.<br
Keywords: Additive manufacturing; PBF-LB/P; Isothermal crystallization; Rheology; Optical properties

Innovative Process Strategies in Powder-Based Multi-Material Additive Manufacturing - Setter, Robert; Hafenecker, Jan; Rothfelder, Richard; Kopp, Sebastian-Paul; Roth, Stephan; Schmidt, Michael; Merklein, Marion; Wudy, Katrin (Journal of Manufacturing and Materials Processing, 2023)
Multi-material additive manufacturing (AM) attempts to utilize the full benefits of complex part production with a comprehensive and complementary material spectrum. In this context, this research article presents new processing strategies in the field of polymer- and metal-based multi-material AM. The investigation highlights the current progress in powder-based multi-material AM based on three successfully utilized technological approaches: additive and formative manufacturing of hybrid metal parts with locally adapted and tailored properties, material-efficient AM of multi-material polymer parts through electrophotography, and the implementation of UV-curable thermosets within the laser-based powder bed fusion of plastics. Owing to the complex requirements for the mechanical testing of multi-material parts with an emphasis on the transition area, this research targets an experimental shear testing set-up as a universal method for both metal- and polymer-based processes. The method was selected based on the common need of all technologies for the sufficient characterization of the bonding behavior between the individual materials.<br
Keywords: additive manufacturing; multi-material additive manufacturing; polymers; metals; shear testing; mechanical testing; powder bed fusion; binder jetting; electrophotography; vibration dispenser

Investigation of the electrophotographic powder deposition through a transfer grid for efficient additive manufacturing - Kopp, Sebastian-Paul; Stichel, Thomas; Roth, Stephan; Schmidt, Michael (Procedia CIRP, 2020)
Until today, the electrophotographic transfer of toner powders has been applied successfully in common printing technology for many years. Utilizing the electrophotographic principle for the transfer of polymer powders in the context of additive manufacturing can give a variety of advantages like e.g. the possibility of generating multi-material components or a reduced consumption of powder. Here, the multiple depositions of powder particle-layers via electrostatic forces to create 3D objects have turned out to be a major challenge. Therefore, a new strategy based on the usage of a grounded transfer grid is examined. Due to its positioning above the generated layers, it makes the powder deposition independent of the already produced part height. For improving the particle transfer, geometrical properties of the grid are analyzed with respect to their influence on the efficiency of the powder deposition. Here, particular attention is paid to the manipulation of the electric transfer field, which is applied for accelerating the charged powder particles. The aim is to enhance the coverage and dimensional accuracy of the deposited powder layers by finding a new transfer structure. <br
Keywords: selective laser melting; electrophotography; polymer powder transfer; multi-material deposition; electric field

Laser plastic welding of additively manufactured components – surface treatment and process adaption for improving the welding result - Sauerwein, Lea; Geiger, René; Kopp, Sebastian-Paul; Tangermann-Gerk, Katja; Roth, Stephan (12th CIRP Conference on Photonic Technologies [LANE 2022], 2022)

Process route adaption to generate multi-layered compounds using vibration-controlled powder nozzles in selective laser melting of polymers - Schuffenhauer, Thomas; Stichel, Thomas; Kopp, Sebastian-Paul; Roth, Stephan; Schmidt, Michael (Lasers in Manufacturing Conference 2019, 2019)
Overcoming the inherent restriction of selective laser melting (SLM) of polymers to the processing of a single material remains a major challenge. Multi-material SLM requires more flexible deposition options to prepare arbitrary powder patterns. Besides the adaption of the recoating system, a suitable melting strategy must be developed. In this report, a previously described vibrational nozzle setup is used for the preparation of a multi-material powder layer. The irradiation strategy is modified to meet the requirements of processing multiple powders: Infrared emitters globally heat the building chamber and induce melting of the low-melting polymer shortly after its deposition. Subsequently, a scanned CO 2 laser beam irradiates the part area, thus melting the high-melting polymer and coalescing both materials. Flowability properties of different polymer powders are optimized for the nozzle-based deposition and analyzed accordingly. Using the adapted SLM process route, multi-layered compounds are generated and characterized regarding surface roughness and microstructure in the boundary zon
Keywords: selective laser melting; polymers; multi-material; powder deposition; vibrational nozzles

Production and analysis of electrically conductive polymer – Carbon-black composites for powder based Additive Manufacturing - Düsenberg, Björn; Tischer, Florentin; Seidel, Anne Marie; Kopp, Sebastian-Paul; Schmidt, Jochen; Roth, Stephan; Peukert, Wolfgang; Bück, Andreas (Procedia CIRP, 2022)
In laser powder bed fusion, micro-particles are selectively fused by a laser to produce parts, layer-by-layer. While this process offers a high freedom of design, the variety of commercially available materials, especially composites are limited. Conductive polymers blends, are very interesting for many applications, especially as sensors with freely definable shape. First, the amount of carbon-black needed to make the composite electrically conductive has to be determined; this limit is called percolation threshold (PT). The PT depends on many properties, such as particle size and shape of both polymer and carbon-black and will be determined experimentally. In this work, polypropylene is dry mixed with different types of micron sized carbon blacks. The PT and the conductivity is determined by means of impedance spectroscopy. Finally, layers are printed to evaluate the processability of the new composite.<br
Keywords: polypropylene; carbon black; percolation threshold

Targeted vibration excitation for increasing the powder deposition efficiency in electrophotographic powder application for Laser-based Powder Bed Fusion of polymers - Kopp, Sebastian-Paul; Medvedev, Vadim; Roth, Stephan (Procedia CIRP, 2022)
High efficiency in terms of powder consumption and the ability to generate multi-material parts using additive manufacturing are key features of the electrophotographic powder application for laser-based powder bed fusion of polymers (PBF-LB/P). The reliable deposition of powder particles onto the build platform is one decisive process step. The aim is to achieve a high degree of coverage and, at the same time, maintain an accurate contour of the deposited powder layer. In addition to the use of a suitable electrical transfer field, which has already been investigated, targeted vibration excitation offers enormous potential for improvement. For this purpose, a mechanical simulation model is set up in this study, which is subsequently validated experimentally. By using the knowledge gained from the simulation, for example with regard to suitable vibration modes, the powder deposition has been significantly improved.<br

Three-Dimensional Multi-material Parts - Kopp, Sebastian-Paul; Roth, Stephan (Progress in Powder Based Additive Manufacturing, 2025)
Generating multi-material polymer parts by means of laser-based additive manufacturing (PBF-LB/P) generally requires the realization of a defined, heterogeneous powder layer consisting of different material